2007
DOI: 10.1111/j.1439-0418.2007.01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent competition or apparent mutualism? An analysis of the influence of rose bush strip management on aphid population in wheat field

Abstract: Apparent competition, mediated by a shared predator, plays a key role in conservation biological control. Appropriate agroecosystems management may favour this type of indirect interaction. In that context, our aim was to test the effect of rose bush [Rosa rugosa (Thunb.)] strips on the building up of aphid populations and of their natural enemies in adjacent cereal habitats. Several aphid species are currently found on Rosa sp. including Metopolophium dirhodum (Walker) for which it is a primary host. Aphid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Movement of some speciÞc parasitoids from noncrop habitats to crop Þelds depends on many factors, ranging from intrinsic biological [e.g., dispersal rate, Weisser and Vö lkl (1997) pointed out low dispersal rate for Lysiphlebus species; host preference, Cameron (1984) showed that A. ervi reared from Acyrthosiphon pisum (Harris) are not so much effective against Sitobion avenae (F.)] to different environmental factors such as presence of alternative food or shelter resources, or suitable aphid hosts in the crop Þelds in comparison with noncrop habitats (Rand et al 2006, Frere et al 2007. Population genetic studies on parasitoid species sourcing from two different hosts together with their habitat stability were undertaken by Antolin et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Movement of some speciÞc parasitoids from noncrop habitats to crop Þelds depends on many factors, ranging from intrinsic biological [e.g., dispersal rate, Weisser and Vö lkl (1997) pointed out low dispersal rate for Lysiphlebus species; host preference, Cameron (1984) showed that A. ervi reared from Acyrthosiphon pisum (Harris) are not so much effective against Sitobion avenae (F.)] to different environmental factors such as presence of alternative food or shelter resources, or suitable aphid hosts in the crop Þelds in comparison with noncrop habitats (Rand et al 2006, Frere et al 2007. Population genetic studies on parasitoid species sourcing from two different hosts together with their habitat stability were undertaken by Antolin et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Grez et al (2010) in Chile illustrates just how speciesspecifi c coccinellid responses can be to various types vegetation bordering agricultural fi elds. However, border vegetation planted to provide supplementary food resources or alternative prey for coccinellids may sometimes impede their timely dispersal into adjacent crops, a phenomenon often referred to as ' apparent competition ' (Frere et al 2007 ). For example, stinging nettle, Urtica dioica , has long been recognized as a reservoir plant for coccinellids (Perrin 1975 ), but such reservoirs cannot benefi t biological control unless beetles leave them and enter crop fi elds.…”
Section: Habitat Managementmentioning
confidence: 99%
“…In other instances, however, aggregation of mobile generalist predators in response to high densities of herbivores in one habitat may lessen predation pressure on other herbivores in other habitats. Frere et al (2007) report, for example, that cereal aphid populations were especially high in wheat plots that were close to strips of rose bush, perhaps because predators and parasitoids aggregated instead to attack aphid populations infesting the roses.…”
Section: Negative Interactions Among Herbivores (Apparent Competition)mentioning
confidence: 99%